A STUDY OF GUIDELINES FOR INTERPRETATION OF COMMUNITY IDENTITY IN SAMCHUK DISTRICT, SUPHANBURI PROVINCE - Suetrong , Jakkawee (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2025)
This article aimed to study the guidelines for interpretation of the community identity in Samchuk District, Suphanburi Province. This research employed a qualitative method. The key informants were residents of Samchuk District, Suphanburi Province. Data were collected through informal interviews, analyzed using content analysis, and described using a descriptive narrative approach. The research findings revealed that the guidelines for interpreting community identity can be divided into two main aspects: 1) Community identity information: Most existing community identities are rooted in the community’s fundamental culture, particularly its history, including ancient temples that have long been part of the community. As for newly created community identities, many communities have established household-based homestays to support community-based tourism. These new identities have emerged as a means to generate income and provide supplementary earnings. The problems and obstacles found include a lack of interest, shortage of successors, and insufficient budget. 2) Interpretation community identity information: The methods of interpretation can be categorized into two types: human-based services and non-human-based services. All communities utilize both methods in parallel to enhance understanding among both community members and outsiders. There is also a need for adequate media and community-based activities. The problems and obstacles found include a lack of communicators, lack of continuous development, and lack of community participation.